WEB-BASED PERFORMANCE MANAGEMENT DECISION SUPPORT SYSTEM - Hartatik Hartatik; Mega A (International Journal of Economy, Education and Entrepreneurship, 2023)
Achievement is an important indicator of the results obtained during education. To find out student achievement, achievement data is needed to make it easier for teachers to see the achievements of each student. In one of the Kalten High Schools, to be precise, SMA which manages the academic and non-academic achievements of students still carried out manually, making it difficult for teachers to choose students with presentations to be included in competition or Olympic activities. To overcome this problem, a web-based achievement management information system was created where this system has 3 actors, namely admins, teachers and principals. The admin actor is in charge of managing data on teachers, students, classes, subjects, grades, extracurriculars, OSN and a list of recommendations for academic and non-academic outstanding students. In the actor, the homeroom teacher manages student data and grades and prints report card scores. While the principal actor can see the data of teachers, classes and subjects. With this system, it is hoped that it can make it easier to manage report card values and achievements. Then the homeroom teacher can only enter the scores of students who are only in their class. Subject teachers do not need to test students or grade students manually because the system will recommend students based on subject scores from daily, UTS and UAS grades with grade weights according to requirements already determined by the school. For the supervisor of extracurricular activities, there is also no need to test students one by one because the system system will recommend students based on several aspects of grades that have been determined for students to be able to represent the school in non-academic competitions such as martial arts, volleyball, basketball and others. After that, the system can automatically recommend students to represent the school in academic and non-academic competitions (OSN), according to the provisions of the competition criteria held with report card scores and student skill scores